Simulations of combustion roar in turbulent attached and lifted turbulent methane jet flames - MARAZIOTI, P.; KOUTMOS, P. (Engineering Transactions, 2009)
The present work presents sample results of preliminary computations of the turbulent aerothermodynamic flow field and of the noise generated by the flame front, due to turbulent fluctuations in the flame (combustion roar), in lifted and attached jet diffusion flames of methane. The two-dimensional (2D) time-dependent numerical model was built based on Reynolds-averaged Navier–Stokes (N-S) equations, equipped with the standard k-e turbulence models to calculate the reacting jet flows. A reactedness – mixture fraction two-scalar exponential PDF model, based on non-premixed flame arguments, was combined with a local Damkohler number extinction criterion to delineate between the reacting and non-reacting regions. Although the inclusion of the effects of premixed flame propagation could help to improve the model, initial comparisons with experimental results suggest adequate qualitative agreement between the computations and reported data. The reasonable agreement obtained for the aerothermodynamic flame characteristics permitted a meaningful computation of the combustion noise (roar) characteristics of the studied flames, in order to address the coupled effects of heat release by the flame and turbulent interactions on the autonomous flame noise generation.